Exploring the Pharmaceutical Care of Pharmacists in China During COVID-19—A National Multicenter Qualitative Study - Wang, Mingxia; Yin, Zhao; Zhang, Wan; Jia, Xuedong; Du, Shuzhang; Li, Jun; Zhang, Xiaojian (Frontiers in Public Health, 2022)
Background: Pharmacists are one of the members of the COVID-19 treatment team, yet only a few single-center studies have mentioned the work experience of pharmacists during the pandemic.Purpose: This study sought to explore in depth the experiences of hospital pharmacists in relation to the provision of pharmacy services during COVID-19 pandemic in mainland China on a national scale.Methods: This is a nationwide, multicenter, phenomenological qualitative study that used purposive sampling method to conduct semi-structured interviews with 11 pharmacy specialists from large-scale comprehensive healthcare institutions in representative provinces of mainland China, and analyzed the interview data using the Colaizzi seven-step methods.Results:We conducted 11 semi-structured interviews, each lasting 25 to 70 minutes. By analyzing the work experiences of pharmacists in COVID-19 designated treatment hospital, five descriptive themes were categorized: 1) drug supply guarantee service; 2) routine clinical pharmacy services; 3) pharmacy services expanded under the epidemic, including remote pharmacy consultation, outpatient drug logistics services, and Popular Science related to SARS-Cov-2 epidemic; 4) drug management loopholes, including management problems with narcotic drugs and donated drugs; and 5）shortcomings in the emergency work of pharmacists.Conclusion: During the COVID-19 epidemic, Chinese hospital pharmacy service system played an important role, however, there were loopholes in the management of narcotic drugs, psychotropic drugs, and donated drugs, and the emergency response capabilities of pharmacists demonstrated deficiencies. The emergency response capacity of hospital pharmacists should be continuously improved in the future to establish more complete pharmacy service system.